SYNTHESIZING WETU TELU ISLAMIC VALUES WITHIN CONTEXTUAL TEACHING AND LEARNING FOR STRENGTHENING RELIGIOUS MODERATION - Masriyani, Riza Febri; Juliana, Rina; Ekafitrianda, J.M.; Delamontano, Eldo (Sekolah Tinggi Agama Islam Al Hidayah, 2026)
This study examines the misalignment between the normative Islamic Religious Education (Pendidikan Agama Islam/PAI) curriculum and the socio-cultural realities of students within the Islamic Wetu Telu tradition in Bayan Traditional Village, North Lombok. Such disconnection may hinder effective educational communication and weaken the development of religious moderation. The study aims to formulate a PAI learning model grounded in the syncretic values of Islam Wetu Telu and to assess its validity and effectiveness through the Contextual Teaching and Learning (CTL) framework. Employing a qualitative Integrated Conceptual–Empirical Study design, this research combines a Systematic Literature Review (SLR) to map core Wetu Telu values onto the seven CTL components and a case study based on in-depth interviews with PAI teachers, the school principal, and traditional leaders at SMPN 6 Bayan. The findings demonstrate that values of tolerance, social cohesion, and ecological awareness can be systematically integrated into CTL-based PAI instruction and implemented through the T5 Program. The model effectively bridges normative Islamic teachings and local cultural practices, particularly within the learning community and modeling components, thereby strengthening students’ religious moderation. The study concludes that integrating Wetu Telu local wisdom into CTL-based PAI offers a context-responsive pedagogical model, although its sustainability requires consistent curriculum support and enhanced teacher cultural competence.